AMINO-2-ETHANE SULFONATO MX2 (M = Zn, Cd, Hg, X = Cl, Br) ADDUCTS: SYNTHESIS AND INFRARED STUDY - Dinora De Barros; Libasse Diop (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Eight amino-2-ethane sulfonato MX2 adducts have been synthesized, their infrared study carried out. The structures are discrete, the anion behaving mainly as a chelating ligand and in the dinuclear adducts as a bichelating ligand.